Factors Influencing Repurchase Intention: A Case Study of PT. Kristal Holidays - Gusti Putu Gede Aditya Putra Wibawa; Ni Putu Evi Wijayanti; I Gede Ngurah Primanda S Rahadiarta (Politeknik Pariwisata Bali, 2024)
This research aims to explore the factors influencing repurchase intention from domestic tourist points of view. This research describes the brand image and service quality as factors that influence repurchase intention. This research uses quantitative methods by examining domestic tourist points of view. The main informants in this research are 103 domestic tourists who previously used the services of PT. Kristal Holidays. This research provides positive results from the factors that influence repurchase intention. There are suggestions that researchers can give to PT. Kristal Holidays to increase the repurchase interest of tourists who use PT. Kristal Holidays services namely by strengthening the brand image and also the quality of service in various aspects of the company.